Tracing the Origins of Personalist Economics to Aristotle and Aquinas. Issue 1 (2nd January 2016) - O'Boyle, Edward J.; Welch, Patrick J.
Abstract : Personalist Economics has identified a central problem in Neoclassical Economics that originates in its representation of the economic agent as homo economicus and its grounding in individualism. Both flaws are directly addressed by Personalist Economics that has a different perspective on human nature as set forth in Personalism. Our remarks are presented in three sections. In the first section we address why individualism is an unsatisfactory philosophical foundation for modern economic theory. In the second section we trace the origins of Personalist Economics to Aristotle and Aquinas. While others, such as Heinrich Pesch and Joseph Schumpeter, played important roles in the evolution of Personalist Economics, here our efforts are restricted to the contributions of Aristotle and Aquinas. In the third section we explore how, in terms of 18 tenets, Personalist Economics and a Personalist economy differ from Mainstream Economics and the individualistic market economy.